Effect of different levels of nitrogen on growth and yield of hybrid maize (Zea mays L.) varieties - Adhikari, Kripa; Bhandari, Sudip; Aryal, Krishna; Mahato, Mohan; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Nitrogen (N) fertilizer is considered as one of the most important factors affecting growth and grain yield of hybrid maize. This study was conducted to determine the effects of different rates of nitrogen and varieties on growth and yield of hybrid maize in Lamahi Municipality, Dang, Nepal from June to October, 2019. Three levels of hybrid maize varieties (10V10, Rajkumar F1 and NMH-731) and four levels of nitrogen (160, 180, 200 and 220 kg N ha-1) were evaluated using two factorial randomized complete block design with three replications. The results showed that grain yield and yield attributing traits of hybrid maize varieties increased with the increasing level of nitrogen from 160 to 220 kg ha-1. The application of nitrogen @ 220 kg N ha-1 produced the highest grain yield (10.07 t ha-1), cob length (16.33 cm), no of rows per cob (14.97), no of grains per row (33.37), cob diameter (4.54), thousand grain weight (276.77 g), stover yield (12.91 t ha-1), biological yield (23.00 t ha-1), harvest index (43.80), gross return (NRs. 208940 ha-1), net return (NRs.104488 ha-1) and B:C ratio (2.001). The hybrid maize variety 10V10 produced the highest grain yield (9.35 t ha-1), net returns (NRs. 91740.66 ha-1) and B:C ratio (1.91) accompanied by the highest cob length (16.25 cm), and as number of grains per row (32.35) as compared to other varieties. This study suggested that maize production can be maximized by cultivating hybrid maize variety 10V10 with the use of 220 kg N ha-1 in inner Terai region of Nepal.